PENGARUH MODEL PEMBELAJARAN “TWO STAY TWO STRAY” TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS V SD IT AL-MUNAWWAR - Nadya Annisa Lubis; Rahmi Seri Hanida; Sahyoni (EDU RESEARCH, 2024)
This research aims to determine the effect of the two stay, two stray learning model on the social studies learning outcomes of fifth-grade students at Al-Munawar Islamic Elementary School. The type of research used in this study is experimental research (experiment research). The research design used in this study is a quasi-experiment design in the form of a nonequivalent control group design. The experimental class is the class that receives treatment in the form of the "Two Stay, Two Stray" learning model, while the control class continues to use conventional learning. Class V Qatar serves as the experimental class, and class V Albania serves as the control class. The data collection instrument used is in the form of multiple-choice tests. The analysis used an independent sample t-test with the assistance of SPSS version 21. The pre- and post-test data underwent a normality test, and the results showed a normal distribution. Subsequently, a hypothesis test was conducted using a parametric statistical test, namely the independent sample t-test with SPSS Statistics 21.0. In the hypothesis test, if the significance value (2-tailed) < 0.05, then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted; if the significance value (2-tailed) > 0.05, then H0 is accepted and Ha is rejected. The result obtained was a significance value (2-tailed) > 0.05, specifically 0.060 < 0.05. In conclusion, (H0) is accepted, indicating that there is an influence of the "Two Stay Two Stray" learning model on students' learning outcomes. It can be concluded that the "Two Stay, Two Stray" learning model has an impact on the social studies learning outcomes of fifth-grade students at Al-Munawwar Islamic Elementary School.